Neutron scattering of porous rocks subjected to uniaxial compression in cryogenic conditions for offshore drilling operations in Arctic - Dr Nadimul Faisal; Dr Reza Sanaee; Dr Tung Lik Lee; Dr Abbie McLaughlin; Dr Rao Martand Singh (ISIS Facility, 2018)
In August 2015, the oil and gas company (Royal Dutch Shell plc) were granted the final permit it needs to begin drilling below the ocean floor for oil in the Arctic. They have been allowed to drill just the top sections of two wells, off the coast of Alaska. Normally, such activities conducted offshore are held to the highest safety, environmental protection, and emergency response standards, but there is little or no published literature available to quantify the relationship between stress-strain and fracture of Arctic rock samples which can be used as a tool for guiding failure operations in geological materials during drilling operations. This work aims to use neutron techniques that can be used to interrogate the internal volume of crystalline geological specimens subjected to stress states at cryogenic temperatures and high pressure resembling geological conditions in Arctic.